2021
DOI: 10.1002/ajh.26114
|View full text |Cite
|
Sign up to set email alerts
|

Young platelet millionaires with essential thrombocythemia

Abstract: The platelet count threshold for World Health Organization classification system-compliant diagnosis of essential thrombocythemia (ET) is ≥450 × 10 9 /L. 1 Extreme thrombocytosis (ExT), on the other hand, is arbitrarily defined by platelet count of ≥1000 × 10 9 /L and occurs in approximately 22% of patients with ET, at time of diagnosis. 2 Note, ExT is most frequent in the context of young patients with ET with incidence rates of 44%/29%/29% in patients aged ≤40, 41-60, and > 60 years respectively. 3 The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
(9 reference statements)
2
7
0
Order By: Relevance
“…In a study evaluating a young ET group (age 18-39 years), among 192 patients (12% in the high-risk group), as many as 107 (55%) received CTR. 16 Similar results were obtained from the analysis of an entire population of young low-risk ET patients (age 18-59 years), where cytoreduction was started in 170 (51%) of patients. 17 In a recent real-world study focused on young patients with a diagnosis of MPN, a total of 444 patients (median age of diagnosis 20.4 years, range 2-25 years) from multiple European centers were evaluated.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In a study evaluating a young ET group (age 18-39 years), among 192 patients (12% in the high-risk group), as many as 107 (55%) received CTR. 16 Similar results were obtained from the analysis of an entire population of young low-risk ET patients (age 18-59 years), where cytoreduction was started in 170 (51%) of patients. 17 In a recent real-world study focused on young patients with a diagnosis of MPN, a total of 444 patients (median age of diagnosis 20.4 years, range 2-25 years) from multiple European centers were evaluated.…”
Section: Discussionsupporting
confidence: 77%
“…Findings similar to those presented in this study have been observed for young patients with ET, with 1 study highlighting that cytoreduction is given willingly in patients with ExT1000, despite a comparable distribution of CV risk factors and lower incidence of AT. 16 Recently, Abu-Zeinah et al presented a database analysis of 40,333 MPN patients followed between 2001-2017. The authors confirmed higher mortality in young PV and ET patients in comparison to the healthy population of the same age.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the reduction of vascular complications may impact survival remains to be demonstrated in appropriate prospective studies. Furthermore, we found two additional independent predictors of mortality in thrombosis-mediated transition, namely platelet count >1000 × 10 9 /L (HR = 5.74, 95% CI = 1.79–18.40, p = 0.003), in line with a previous observation [ 13 ], and the incident arterial vs. venous thrombosis (HR = 4.43, 95% CI = 1.04–18.91, p = 0.044).…”
supporting
confidence: 92%
“…Alessandra Carobbio 1 , Alessandro Maria Vannucchi 2 , Elisa Rumi 3,4 , Valerio De Stefano 5,6 , Alessandro Rambaldi 7,8 , Giuseppe Carli 9 , Maria Luigia Randi 10 , Heinz Gisslinger 11 , Francesco Passamonti 12 , Juergen Thiele 13 , Naseema Gangat 14 , Ayalew Tefferi 14 and Tiziano Barbui Hematology and Bone Marrow Transplant Unit, ASST Papa Giovanni XXIII, Bergamo, Italy. 8 Department of Oncology and Hematology, University of Milan, Milan, Italy.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…The current study complements our recent report on 192 young patients (age <40 years) with ET where ExT was associated with CALR mutation, lower likelihood of presentation with thrombosis and shortened overall and leukemia-free survival. 9 In both the current and the aforementioned study, 9…”
mentioning
confidence: 81%